Seasonal and Temporal Influence on Polycyclic Aromatic Hydrocarbons in the Red Sea Coastal Water, Egypt - Mohamed El-Naggar (MDPI AG, 2021)
This study investigated seasonal variation, spatial distribution, sources, composition and potential ecological risks of 16 polycyclic aromatic hydrocarbons (PAHs) in Red Sea coastal water. Surface seawater samples were collected at fourteen different locations. The sum of 16 PAHs concentrations in Red Sea showed clear variation between seasons, ranged from 1.08–6.10, 0.79–50.86, 1.37–54.47 and 0.21–7.18 μg/L in summer, autumn, winter, and spring respectively. PAHs levels in Red Sea coastal waters were relatively high at certain sites during autumn and winter seasons. They could be classified as highly polluted by PAHs contaminants (>10 μg/L). According to the diagnostic ratios measured, the majority of PAHs in this study originated from pyrogenic sources, while minor amounts originated from petrogenic sources. Four rings PAHs accounted for more than 64% of the total PAHs studied. PAHs pose a high ecological risk along the period of study, according to the ecological risk assessment by Risk quotients (RQNCs and RQMPCs).